Consumer education in creating a consumer conscious nation - Mazlan, Dzulkarnain; Md. Redzuan, Ahmad; Abu Bakar, Darussalam (Elsevier Ltd., 2014)
Consumers are exposed to the risks and threats due to the usage of unsafe or substandard products or services.However, they should empowered themselves with the consumerism knowledge through formal or informal education. It can help the society to understand what their role in being the conscious consumer.The purpose of this paper is to know the consumer education in Malaysia has achieved their target in a way to create the awareness among public. Based on findings, it can be concluded that consumer education was not commencing in the streamline education system whether in primary, secondary or tertiary.